Baricitinib for systemic lupus erythematosus: a double-blind, randomised, placebo-controlled, phase 3 trial (SLE-BRAVE-I). Issue 10381 (25th March 2023) - Morand, Eric F; Vital, Edward M; Petri, Michelle; van Vollenhoven, Ronald; Wallace, Daniel J; Mosca, Marta; Furie, Richard A; Silk, Maria E; Dickson, Christina L; Meszaros, Gabriella; Jia, Bochao; Crowe, Brenda; et al.
Summary: Background: Baricitinib is an oral selective inhibitor of Janus kinase 1 and 2 approved for the treatment of rheumatoid arthritis, atopic dermatitis, and alopecia areata. In a 24-week phase 2 study in patients with systemic lupus erythematosus (SLE), baricitinib 4 mg significantly improved SLE disease activity compared with placebo. The objective of this trial was to evaluate the efficacy and safety of baricitinib in patients with active SLE in a 52-week phase 3 study. Methods: In a multicentre, double-blind, randomised, placebo-controlled, parallel-group, phase 3 study, SLE-BRAVE-I, patients (aged ≥18 years) with active SLE receiving stable background therapy were randomly assigned 1:1:1 to baricitinib 4 mg, 2 mg, or placebo once daily for 52 weeks with standard of care. Glucocorticoid tapering was encouraged but not required per protocol. The primary endpoint was the proportion of patients reaching an SLE Responder Index (SRI)-4 response at week 52 in the baricitinib 4 mg treatment group compared with placebo. The primary endpoint was assessed by logistic regression analysis with baseline disease activity, baseline corticosteroid dose, region, and treatment group in the model. Efficacy analyses were done on a modified intention-to-treat population, comprising all participants who were randomly assigned and received at least one dose of investigational product. Safety analyses were done on all randomly assigned participants who received at least one dose of investigational product and who did not discontinue from the study for the reason of lost to follow-up at the first post-baseline visit. This study is registered with ClinicalTrials.gov, NCT03616912 . Findings: 760 participants were randomly assigned and received at least one dose of baricitinib 4 mg (n=252), baricitinib 2 mg (n=255), or placebo (n=253). A significantly greater proportion of participants who received baricitinib 4 mg (142 [57%]; odds ratio 1·57 [95% CI 1·09 to 2·27]; difference with placebo 10·8 [2·0 to 19·6]; p=0·016), but not baricitinib 2 mg (126 [50%]; 1·14 [0·79 to 1·65]; 3·9 [–4·9 to 12·6]; p=0·47), reached SRI-4 response compared with placebo (116 [46%]). There were no significant differences between the proportions of participants in either baricitinib group reaching any of the major secondary endpoints compared with placebo, including glucocorticoid tapering and time to first severe flare. 26 (10%) participants receiving baricitinib 4 mg had serious adverse events, 24 (9%) participants receiving baricitinib 2 mg, and 18 (7%) participants receiving placebo. The safety profile of baricitinib in participants with SLE was consistent with the known baricitinib safety profile. Interpretation: The primary endpoint in this study was met for the 4 mg baricitinib group. However, key secondary endpoints were not. No new safety signals were observed. Funding: Eli Lilly and Company.